Strengthening capacity of extension officers in gender-responsive bean research, digital extension and agribusiness in Laikipia and Nyeri Counties, Kenya - Nchanji, Eileen Bogweh; Karanja, David; Waswa, Boaz Shaban; Aseete, Paul; Kasubri, Fadhili; Mutuli, Wincaster; Korir, Vicky; Ketiem, Patrick (2023)
Although seed is an integral part of the agri-food system, it is often unavailable and unaffordable to smallholder farmers in rural areas, especially women and vulnerable groups. In addition, the poor extension system of getting seeds and information to farmers remains a drawback to adoption and increased productivity. Further, increased climate variability exposes these vulnerable groups to risks like pests and diseases. This calls for more concerted and focused strategies by researchers and development actors to mitigate these challenges through robust partnerships and training. The Kenya Agricultural Livestock Research Organization (KALRO) and the Alliance of Bioversity International and CIAT, The Alliancethrough the Seed Equal Initiative, the Gender Equality Initiative, the Ukama Ustawi (UU): Diversification for Resilient Agri-food in East and Southern Africa organized a two-day training of extension officers from Laikipia and Nyeri counties in Kenya in gender-responsive seed systems, digitalised agribusiness and agronomy. The training was attended by 16 officers (5 men and 11 women).